The Perfect Predator: A Scientist's Race to Save Her Husband, by Drs. Steffanie Strathdee and Thomas Patterson - Pia D. M. MacDonald (Ubiquity Press, 2020)
This is a book review of "The Perfect Predator: A Scientist's Race to Save Her Husband" by Drs. Steffanie Strathdee and Thomas Patterson.